2015
DOI: 10.1590/1983-1447.2015.esp.55284
|View full text |Cite
|
Sign up to set email alerts
|

Análise epidemiológica da hanseníase em um estado endêmico do nordeste brasileiroAnálisis epidemiológica de la lepra en estado endémico del nordeste brasileño

Abstract: RESUMO Objetivo Caracterizar a tendência, segundo indicadores epidemiológicos e operacionais, de endemia da hanseníase no Estado da Paraíba no período de 2001-2011, com projeções para os anos de 2012-2014. Métodos Estudo epidemiológico de série temporal, retrospectivo e documental, realizado com 10.476 casos notificados de hanseníase, diagnosticados entre 2001-2011, nos 223 municípios do Estado paraibano. Utilizou-se para composição e análise dos resultados dois indicadores epidemiológicos e um indicador o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
1
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 10 publications
2
11
1
20
Order By: Relevance
“…In most cases, the bacilloscopy results were negative, in agreement with other authors (6) . According to the Ministry of Health, bacilloscopy, a relatively simple test used to classify cases of Hansen's disease, is one criterion used to determine leprosy treatment (3) .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In most cases, the bacilloscopy results were negative, in agreement with other authors (6) . According to the Ministry of Health, bacilloscopy, a relatively simple test used to classify cases of Hansen's disease, is one criterion used to determine leprosy treatment (3) .…”
supporting
confidence: 91%
“…Leprosy mainly affects individuals during the economically active periods of their lives; generally, this period ranges from 20 to 60 years of age, although studies differ with respect to the most affected age groups (6) . In the present study, individuals in this most economically productive age range accounted for 54% of the total patient population.…”
mentioning
confidence: 99%
“…Once this has crippling features, becomes of great importance to completion of the assessment of the degree of disability of patients during treatment and after discharge in order to minimize the risk of loss in the ability to work and consequently on economic, social and psychological damage to the individual. 17,19,20 In research conducted in the northeast of Diamantina/ MG 15 , was observed more people outside the labour market (46,5%) of which 33,3% needed clearance from their labour activities due to the complications generated by Hansen's disease.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 .Não obstante, outros estudos realizados na Paraíba e em Santa Catarina vão de encontro aos resultados encontrados, indicando a maior prevalência do sexo feminino 10,22 . No que concerne à cor da pele, os pardos foram acometidos mais frequentemente, em concordância com a literatura analisada 21,23,24 . Quanto à escolaridade, verificou-se maior proporção de pacientes com ensino fundamental incompleto, reiterando estudos publicados recentemente 10,23,25 .…”
unclassified
“…No que concerne à cor da pele, os pardos foram acometidos mais frequentemente, em concordância com a literatura analisada 21,23,24 . Quanto à escolaridade, verificou-se maior proporção de pacientes com ensino fundamental incompleto, reiterando estudos publicados recentemente 10,23,25 . Esses resultados são reflexo da precariedade socioeconômica associada à endemia de hanseníase, que acomete mais pessoas com baixo nível de escolaridade, deficiências nutricionais e condições desfavoráveis de habitação e higiene 23 .…”
unclassified